2019
DOI: 10.1007/s42452-019-1862-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of dual water supply using rooftop rainwater harvesting and groundwater systems

Abstract: The aim of this study was to gain a better understanding on dual water supply system consisting of rainwater and groundwater. The pilot study of the designed system was carried out at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Second, bathing activities are, to our knowledge, investigated for the first time with lower quality standard requirements than drinking standard. Third, contrary to most researches on dual water systems that are focused on the use of reclaimed water [22,23] and the comparison of the energy efficiency between dual and conventional systems, the present work assesses simultaneously the material, energy, and cost savings induced by the differentiation of water quality by usage. The integrated model EVALEAU is applied to a conventional treatment system of French municipal water supply as an illustration of how material, cost, and energy can be saved when degrading the water quality requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, bathing activities are, to our knowledge, investigated for the first time with lower quality standard requirements than drinking standard. Third, contrary to most researches on dual water systems that are focused on the use of reclaimed water [22,23] and the comparison of the energy efficiency between dual and conventional systems, the present work assesses simultaneously the material, energy, and cost savings induced by the differentiation of water quality by usage. The integrated model EVALEAU is applied to a conventional treatment system of French municipal water supply as an illustration of how material, cost, and energy can be saved when degrading the water quality requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Barker et al [22] showed the reuse of treated wastewater effluent for non-potable purposes in North Carolina could consume less energy than when using the potable network. Rainwater harvesting potential was investigated in Malaysia [23] and Vietnam [24] whereas the deterioration of source water quality in China [25] made a dual water distribution system both more economical and practical than the conventional system. For developed countries, the investigation of dual water systems is important in the context of aging infrastructure as a possibility for improving the efficiency of the current centralized municipal water system [26].…”
Section: Introductionmentioning
confidence: 99%
“…In India per capita water availability is 70% reduced from 1951 to 2011 (Dubbudu, 2016). To support the sustainable development and reduced the pressure on the ground water, rain water harvesting from the rooftop and its storage can be produced as best alternate for the individual houses in urban area (Rahmat et al, 2020). Collected water has been utilised for both portable and non-portable (like urinal flushing, toilet, laundry) purposes (Santos and Pinto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the rooftop water 4 collected by rainwater harvesting systems is used for non-potable demands (such as industrial processing) and potable demands (such as cooking). 5 Amongst these demands, energy harvesting from rainfall during the rainwater harvesting process has attracted significant attention in recent years. Rainwater energy harvesting can not only convert the mechanical energy from falling raindrops into electricity for powering sensors and other electronics devices but can also effectively solve ground collapse problems caused by the impact of rainwater.…”
Section: Introductionmentioning
confidence: 99%
“…It is suitable for all types of buildings ranging from residential to commercial and industrial structures. Typically, the rooftop water 4 collected by rainwater harvesting systems is used for non‐potable demands (such as industrial processing) and potable demands (such as cooking) 5 . Amongst these demands, energy harvesting from rainfall during the rainwater harvesting process has attracted significant attention in recent years.…”
Section: Introductionmentioning
confidence: 99%